Dietary fat overload reprograms brown fat mitochondria - Lettieri Barbato, Daniele; Tatulli, Giuseppe; Vegliante, Rolando; Cannata, Stefano M.; Bernardini, Sergio; Ciriolo, Maria R.; Aquilano, Katia (Frontiers in Physiology, 2015)
Chronic nutrient overload accelerates the onset of several aging-related diseases reducing life expectancy. Although the mechanisms by which overnutrition affects metabolic processes in many tissues are known, its role on BAT physiology is still unclear. Herein, we investigated the mitochondrial responses in BAT of female mice exposed to high fat diet (HFD) at different steps of life. Although adult mice showed an unchanged mitochondrial amount, both respiration and OxPHOS subunits were strongly affected. Differently, offspring pups exposed to HFD during pregnancy and lactation displayed reduced mitochondrial mass but high oxidative efficiency that, however, resulted in increased bioenergetics state of BAT rather than augmented uncoupling respiration. Interestingly, the metabolic responses triggered by HFD were accompanied by changes in mitochondrial dynamics characterized by decreased content of the fragmentation marker Drp1 both in mothers and offspring pups. HFD-induced inactivation of the FoxO1 transcription factor seemed to be the up-stream modulator of Drp1 levels in brown fat cells. Furthermore, HFD offspring pups weaned with normal diet only partially reverted the mitochondrial dysfunctions caused by HFD. Finally these mice failed in activating the thermogenic program upon cold exposure. Collectively our findings suggest that maternal dietary fat overload irreversibly commits BAT unresponsiveness to physiological stimuli such as cool temperature and this dysfunction in the early stage of life might negatively modulates health and lifespan.